Validasi Eksperiment of a 50Wp Off-Grid Solar Power Plant Using a Linear Actuator Solar Tracker System - Maulana Adi Prakoso; Muhammad Fajry Setyawan; Komarudin Komarudin; Asri Nugrahanti (International Journal of Industrial Innovation and Mechanical Engineering, 2026)
Electrical energy is essential for daily life in Indonesia, particularly in remote areas where access to the national grid remains limited. Off-grid solar power systems offer a promising solution, although fixed photovoltaic (PV) installations are less efficient because they cannot follow the sun’s movement. This study experimentally evaluated the performance of a 50 Wp off-grid solar power system equipped with a linear actuator-based solar tracker and assessed its structural safety using Finite Element Analysis (FEA) in SolidWorks. A quantitative experimental approach compared a fixed PV system positioned at a 34° angle with a solar tracker system. Data on PV voltage, solar flux, and battery voltage were collected every 30 minutes between 11:00 a.m. and 2:00 p.m. Results showed that the solar tracker maintained more stable power generation and reduced afternoon output losses, producing an average power of 15.83 W compared with 6.79 W from the fixed system. Battery charging was also faster using the tracker. FEA results confirmed that all support structures met safety standards, with maximum stresses below the ASTM A36 yield strength and acceptable Factors of Safety. These findings demonstrate that linear actuator-based solar trackers significantly improve off-grid solar power performance while maintaining structural reliability.